Fibronectin Containing Extra Domain A Induces Plaque Destabilization in the Innominate Artery of Aged Apolipoprotein E–Deficient Mice. Issue 3 (March 2018) - Doddapattar, Prakash; Jain, Manish; Dhanesha, Nirav; Lentz, Steven R.; Chauhan, Anil K.
Abstract : Objective—: Fibronectin containing extra domain A (Fn-EDA) is an endogenous ligand of TLR4 (toll-like receptor 4) and is abundant in the extracellular matrix of advanced atherosclerotic lesions in human and mice. Irrespective of sex, deletion of Fn-EDA reduces early atherosclerosis in apolipoprotein E–deficient (Apoe −/− ) mice. However, the contribution of Fn-EDA in advanced atherosclerosis remains poorly characterized. We determined the contribution of Fn-EDA in advanced atherosclerotic lesions of aged (1-year-old) Apoe −/− mice. Approach and Results—: Plaque composition was determined in the innominate artery, a plaque instability site that is known to mimic several histological features of vulnerable human plaques. Female Apoe −/−, Fn-EDA −/− Apoe −/−, TLR4 −/− Apoe −/−, and Fn-EDA −/− TLR4 −/− Apoe −/− mice were fed a high-fat Western diet for 44 weeks. Fn-EDA −/− Apoe −/− mice exhibited reduced plaque size characterized by smaller necrotic cores, thick fibrous caps containing abundant vascular smooth muscle cells and collagen, reduced CD68/MMP9 (matrix metalloproteinase 9)-positive content, less accumulation of MMP-cleaved extracellular matrix aggrecan, and decreased vascular smooth muscle cell and macrophage apoptosis ( P <0.05 versus Apoe −/− mice). Together these findings suggest that Fn-EDA induces plaque destabilization. Deletion of TLR4 reduced histological features of plaque instability in Apoe −/− mice but did not further reduce features of plaque destabilization in Fn-EDA −/− Apoe −/− mice, suggesting that TLR4 may contribute to Fn-EDA–induced plaque destabilization. Fn-EDA potentiated TLR4-dependent MMP9 expression in bone marrow–derived macrophages, suggesting that macrophage TLR4 may contribute to Fn-EDA–mediated plaque instability. Conclusions—: Fn-EDA induces histological features of plaque instability in established lesions of aged Apoe −/− mice. The abundance of Fn-EDA in advanced atherosclerotic lesions may increase the risk of plaque destabilization. Abstract : Supplemental Digital Content is available in the text.